Search for rare decays of Z and Higgs bosons to J / ψ and a photon in proton-proton collisions at √s = 13 TeV - KAYA, MİTHAT (My University, 2019)
© 2019, CERN for the benefit of the CMS collaboration.A search is presented for decays of Z and Higgs bosons to a J / ψ meson and a photon, with the subsequent decay of the J / ψ to μ+μ-. The analysis uses data from proton-proton collisions with an integrated luminosity of 35.9fb-1 at s=13TeV collected with the CMS detector at the LHC. The observed limit on the Z → J / ψγ decay branching fraction, assuming that the J / ψ meson is produced unpolarized, is 1.4 × 10 - 6 at 95% confidence level, which corresponds to a rate higher than expected in the standard model by a factor of 15. For extreme-polarization scenarios, the observed limit changes from - 13.6 to + 8.6 % with respect to the unpolarized scenario. The observed upper limit on the branching fraction for H → J / ψγ where the J / ψ meson is assumed to be transversely polarized is 7.6 × 10 - 4, a factor of 260 larger than the standard model prediction. The results for the Higgs boson are combined with previous data from proton-proton collisions at s=8TeV to produce an observed upper limit on the branching fraction for H → J / ψγ that is a factor of 220 larger than the standard model value.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)